A practical framework for implementing and evaluating integrated management of marine activities. (1st July 2019) - Stephenson, Robert L.; Hobday, Alistair J.; Cvitanovic, Christopher; Alexander, Karen A.; Begg, Gavin A.; Bustamante, Rodrigo H.; Dunstan, Piers K.; Frusher, Stewart; Fudge, Maree; Fulton, Elizabeth A.; Haward, Marcus; Macleod, Catriona; et al.
Abstract: Despite frequent calls for Integrated Management (IM) of coastal and marine activities, there is no consensus on the 'recipe' for successful adoption and implementation, and there has been insufficient evaluation of successes and failures of IM to date. The primary rationale for IM is to overcome four major deficiencies of sector-based management: a) management of diverse activities by different agencies using different approaches, b) management generally focused on a subset of primarily ecological objectives that do not properly articulate or evaluate social, cultural, economic and institutional objectives, c) no mechanisms to evaluate or advise on trade-offs among objectives of activities in relation to objectives and d) no mechanisms to evaluate the cumulative effects of all managed activities. To help overcome this gap in knowledge, here we draw on our collective experiences working in Australia and Canada to develop and articulate a framework to help guide the practical implementation and evaluation of IM, which we define as: ' An approach that links (integrates) planning, decision-making and management arrangements across sectors in a unified framework, to enable a more comprehensive view of sustainability and the consideration of cumulative effects and trade-offs.' We argue that IM will be most easily and effectively achieved by linking and modifying existing sector-based plans in an overarching IM initiative that has nine key features: 1) Recognition of need for IM, 2) A shared vision by stakeholders and decision-makers for IM, 3) Appropriate legal and institutional frameworks for coordinated decision-making, 4) Sufficient and effective processes for stakeholder engagement and participation, 5) A common and comprehensive set of operational objectives, 6) Explicit consideration of trade-offs and cumulative impacts, 7) Flexibility to adapt to changing conditions, 8) Processes for ongoing review and refinement, and 9) Effective resourcing, capacity, leadership and tools. Drawing on these features we then articulate a process for the implementation and evaluation of IM that recognises five phases: i) Preconditions and drivers of change, ii) Intentional design and institutional rearrangement, iii) Enablers and disablers iv) An implemented IM process, and v) Review of IM performance and modification. Combination of the nine features of IM with the five phases in IM development provides a framework for implementation and a lens for evaluation of IM processes. We suggest that this framework provides a guide to the appropriate design of practical IM, which will assist in overcoming the current management deficiencies and improve the sustainability of marine resources in the face of change. Highlights: Sector-based management cannot adequately address trade-offs and cumulative effects. Integrated planning and management is required for holistic sustainability. Integrated Management can build on existing management arrangements across sectors in a unified way. This paper provides a 'recipe' or framework for successful implementation of Integrated Management. Nine key features and five phases of implementation provide a lens for evaluation of Integrated Management.